PROSES PENCIPTAAN TARI PUJIAN RUMPUT HIJAU: STUDI KASUS TIM INLA INTERNASIONAL BI CAO - Neolaka, Melki Jemri Edsion (Jurnal KATA, 2018)
Dance is like a living organism that is maintained by a pattern of continuous change. The changing from the beginning and ending of its sequencescreate an internal rhythm, structure, space design, and power-breaking as its characteristic in every creations. That creations emerge as a manifestation of the expression of the soul through motion events. The choreography of creative dance comes from imagination and intuition produced to provide aesthetic stimulus that will always be in the audience's memories.This research is qualitative research with Action Research method.Action research is an initial step in the form of a research design that describes, interprets and explains a social situation at the same time by making changes or interventions for the purpose of improvement or participation.This research contributesto practical problem solving for an urgent problematic situation in the development of dance creation methods of INLA International Bicao Team.The five phases of the creative process offered by researchers are the Alma Hawkins Creation Method which consists of; Sensing, Feeling, Imaging, Transforming, and Forming. These five phases are expected to be able to answer the problem of dance creation process in Creativity activities of INLA International Bi Cao Team which is related to the construction of the work of production and the technique of contemporary nuances.Tari seperti organisme hidup yang dipertahankan oleh suatu pola perubahan yang berkeseinambungan. Rentetan awal dan akhir dari perubahan ini menciptakan ritme internal, struktur, desain ruang, dan curahan tenaga yang khas pada setiap karya yang muncul sebagai perwujudan ekspresi jiwa melalui peristiwa-peristiwa gerak.Koreografi tari yang kreatif hadir dari imajinasi dan intuisi yang diproduksi untuk memberikan stimulus estetika yang akan selalu berada dimemori sang penikmat. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitan kualitatif dengan metode Action Research. Penelitian tindakan sebagai langkah awal berbentuk rancangan penelitian yang mendeskripsikan, menginterpretasi dan menjelaskan suatu situasi sosial pada waktu yang bersamaan dengan melakukan perubahan atau intervensi dengan tujuan perbaikan atau partisipasi. Dalam hal ini, memberikan andil pada pemecahan masalah praktis dalam situasi problematik yang mendesak dalam pengembangkan metode penciptaan tari di tubuh tari Tim INLA Internasional Bicao. Lima fase dari proses kreatif yang ditawarkan oleh peneliti adalahMetode Penciptaan Alma Hawkins yang terdiri dari ; Sensing, Feeling, Imaging, Transforming, dan Forming yang diharapkan mampu menjawab permasalahan proses penciptaan tari di dalam kegiatan kreativitasTim INLA Internasional Bi Caoyang berkaitan dengan konstruksi produksi karya dan teknik kepenarian dalam nuansa-kontemporer.